Family interactions in toddlerhood influence social competence in preschool age: Accounting for genetic and prenatal influences - Ramos, Amanda M.; Shewark, Elizabeth A.; Reiss, David; Leve, Leslie D.; Natsuaki, Misaki N.; Shaw, Daniel S.; Ganiban, Jody M.; Neiderhiser, Jenae M. (Frontiers in Psychology, 2022)
Identification of early promotive and risk factors for social competence is important for fostering children’s successful social development; particularly given social competence is essential for children’s later academic and psychological well-being. While research suggests that the early parent–child relationship, genetics, and prenatal influences are associated with social competence, there is less research considering how these factors may operate together to shape children’s social competence in early childhood. Using a genetically informed sample from the Early Growth and Development Study (N = 561), we examined multiple levels of influence (i.e., genetic, prenatal, parenting, and child characteristics) on children’s social competence at 4.5 years old. Results from structural equation models showed adoptive mother overreactivity at 18 months was positively associated with child dysregulation at 27 months, which, in turn, was associated with lower levels of social competence at 4.5 years. Also, child reactivity at 18 months was independently associated with higher levels of adoptive mother overreactivity at 27 months, which, in turn, was associated with lower levels of social competence at 4.5 years. Finally, we found an evocative effect on adoptive fathers’ overreactivity at 18 months such that prenatal birth mother distress was negatively associated with adoptive fathers’ overreactivity at 18 months. Overall, this study found evidence for genetic influences, and bidirectional associations between parent and child in toddlerhood that are related to lower levels of social competence when children were 4.5 years old. We also found that the prenatal environment was associated with parenting, but not with child behavior directly. This study’s ability to simultaneously examine multiple domains of influence helps provide a more comprehensive picture of important mechanisms and developmental periods for children’s early social competence.